PERSEPSI MAHASISWA TERHADAP LAYANAN NOKIA LIFE TOOL SEBAGAI INOVASI MEDIA INFORMASI PERTANIAN - Yuanita, Suzyant; h, Hadiyanto (Sodality: Jurnal Sosiologi Pedesaan, 2010)
Nokia Life Tools is an innovation in agricultural sector which provide relevant information needed by farmers. One of the consequences of innovation is justification as action by the stakeholders. Agronomy and Horticultural Department students in this case are acting as one of the stackholders for the agricultural sector. The purpose of this study is to find out what the perception of students in the Agronomy and Horticultural Department class of 2006 about Nokia Life Tools watched by its characteristic as an innovation to agricultural sector. Beside that this study also have the purpose to understand the relation between internal and external factors from the Agronomy and Horticultural Department class of 2006 students with the perception about Nokia Life Tools.The result of this study shows that students in the Agronomy and Horticultural Department class of 2006 think that Nokia Life Tools giving an average advantage level, quite fit for agricultural sector, quite complicated, quite easy to be tried, and also quite easy for the result to be observed. Other result is the internal factor that related to the students in the Agronomy and Horticultural Department class of 2006 perception is the origin of the students and the students awareness level about Nokia Life Tools., and the external factor is the students exposure level of the Nokia Life Tools advertisement.